Stress-Strain Curve of Fibrous Concrete in Compression - Aziz, Omer Qarani; Abdul-Ahad, Ramzi B. (Sulaimani Journal for Pure and Applied Sciences, 2002)
A simple experimental technique was used to obtain the stress-strain curves of the normal weight concrete containing steel fibers. An analytic expression for the stress-strain relationship of the normal weight fibrous concrete is developed. Equations to predict the ultimate strain and the block stress parameters of the fibrous concrete were developed to reflect experimental results. The analytic expression has four constants, which depend on the properties of both the ascending and descending portion of the stress-strain curve and can be evaluated from the knowledge of the four key points of the curve.
Keywords: Concrete; Compression; Fiber; Normal Weight; Stress; Strain